Penghalang Oksidatif Akar Padi terhadap Keracunan Besi - Sujinah, Sujinah; Diniaty, Rossa (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Sujinah, Diniaty R. 2022. Oxydative barrier of rice roots against iron toxicity. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 495-503. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Most of the mineral soils in swamps contain iron and under anaerobic and low pH, Fe3+ is reduced to Fe2+ which is easily soluble and absorbed by roots. Excessive of Fe2+ cause toxicity plants which will interference various plant metabolism. Iron is absorbed by roots into the root tissue, then transported through the xylem to the shoots. Precipitation of Fe2+ in plant tissues causes excessive production of reactive oxygen species (ROS), especially hydroxyl radical (OH-) through Fenton reacion, thereby damaging cell structures, membranes, DNA, and protein in plants. This paper will discuss how plant can avoid excess iron in the root area. The root tip is the first part that will get iron toxicity. At the tip of the root (root cap) produces cells called root border cells (RBCs) which play a role in protecting the roots from abiotic stress. In flooded conditions, there is a release of oxygen into the rhizosphere by aerenchyma, or called radial oxygen loss (ROL) which will induce the formation of iron plaque. The formation of iron plaque will the interfere with the absorption of root nutritions. One of the tolerance mechanisms that occur at the root level is the exclusion evasion through the ROL barrier and the entry of iron by forming lignin in the root cell wall.